Frequency and Pattern of Thyroid Dysfunction in Patients with Polycystic Ovary Syndrome - Naz, Sadaf; khan, khurshid Ahmad; Umer, Amina; Raza, Muhammad Tabish; Nasir, Khalid Mehmood; Hussain, Imtiaz (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the frequency and pattern of thyroid dysfunction in patients with polycystic ovary syndrome.Study Design: Cross-sectional study.Place and Duration of Study: Department of Endocrinology, Jinnah Hospital, Lahore Pakistan, from Jan from Jun 2017.Methodology: Seventy-seven patients diagnosed with PCOS, based on Rotterdam criteria, were enrolled in the study. Thyroid function status was evaluated using measurement of serum thyroid-stimulating hormone (TSH), free T3, T4 and anti-thyroperoxidase (anti-TPO) antibodies.Results: The mean age of the study population was 29.0±9.2 years. Out of 77 females with PCOS, 63(81.8%) were euthyroid, five (6.5%) patients were diagnosed with primary hypothyroidism, and nine (11.7%) were found to have subclinical hypothyroidism. Anti-TPO antibodies were detected in 18 patients (23.4%), including 12(19.0%) euthyroid females.Conclusion: Thyroid dysfunction was found among patients with PCOS. Evidence of autoimmunity was seen even in euthyroid patients.